2017
DOI: 10.1111/jocn.13924
|View full text |Cite
|
Sign up to set email alerts
|

To break the weight gain—A qualitative study on the experience of school nurses working with overweight children in elementary school

Abstract: The school nurses' health promotion needs to focus on how to break weight gain in overweight children. In this work, the nurses' sensitiveness seems pivotal. Further research is needed on school nurses' work with health promotion and support of overweight children concerning how to perform efficient communication and cooperation with the children and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 28 publications
4
28
0
2
Order By: Relevance
“…Compared with earlier studies conducted in the United States (14,15), in our study, obesity was diagnosed more frequently and overweight and obesity were adequately identified both by school physicians and nurses. This aligns with the knowledge that school nurses feel responsible to recognise children with overweight (11).…”
Section: Obesity Diagnosis and Screening Of Overweightsupporting
confidence: 59%
See 2 more Smart Citations
“…Compared with earlier studies conducted in the United States (14,15), in our study, obesity was diagnosed more frequently and overweight and obesity were adequately identified both by school physicians and nurses. This aligns with the knowledge that school nurses feel responsible to recognise children with overweight (11).…”
Section: Obesity Diagnosis and Screening Of Overweightsupporting
confidence: 59%
“…Thus, reality seems to differ from ambition, as healthcare providers’ self‐reports of screening and managing childhood obesity are rosier than their corresponding documentation in medical charts . School nurses are in the forefront in identifying obesity, and they play a key role in its school‐based treatment . Nurses also confront numerous barriers in the practical implementation of obesity intervention .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian menunjukkan bahwa penting meningkatkan kesadaran orang tua tentang obesitas pada anak melalui promosi dan pendidikan kesehatan yang komprehensif (Syahrul et al, 2016). Perawat harus memberikan motivasi kepada anak-anak dalam perubahan gaya hidup menjadi gaya hidup sehat (Thorstensson, Blomgren, Sundler, & Larsson, 2018).…”
Section: Pendahuluanunclassified
“…One qualitative study from southern Sweden discovered that school nurses work together with the families to stop the trajectory of weight gain rather than work towards a weight loss. 14 Another qualitative study from central Sweden also found that the relationship with the parents and children was important in their role of referring the child to treatment for overweight or obesity. 15 To our knowledge there are no reports or studies on how school nurses in northern Sweden work with childhood obesity.…”
Section: Introductionmentioning
confidence: 99%